2020
DOI: 10.1177/1049731520975860
|View full text |Cite
|
Sign up to set email alerts
|

The Online Adaptation and Outcomes of a Family-Based Intervention Addressing Substance Use Disorders

Abstract: Purpose: This article compares outcomes of a family-based prevention program from its original in-person mode to an online mode in response to the COVID-19 pandemic. Celebrating Families!™ is designed to improve parenting skills, family functioning, and family relationships to break the cycle of substance use problems. Method: This mixed-methods, quasi-experimental study compared outcomes of in-person and online treatment conditions and content analysis of open-ended responses to a satisfaction survey. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Social workers were required to have a paradigm shift in adopting ICT to deliver formal service by having diverse ICT options, a client-driven approach, and creativity (Mishna, Milne, Bogo, & Pereira, 2020). Practice examples included the following: telehealth in an Australian child adolescent mental health clinic (de Kam, 2020); an online family-based prevention program in the US (Cohen & Tisch, 2021); virtual social work care with older black adults in Canada (Giwa, Mullings, & Karki, 2020); a social media campaign in Lebanon titled “Humans discriminate, Viruses don’t” (Badran, 2020); and the use of the Internet to care for cadets by military social workers in Taiwan (Chiu & Yu, 2020). Technology training and creative strategies would be necessary for social workers to assist older adults in learning and using new telehealth and social engagement technologies (Gibson et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Social workers were required to have a paradigm shift in adopting ICT to deliver formal service by having diverse ICT options, a client-driven approach, and creativity (Mishna, Milne, Bogo, & Pereira, 2020). Practice examples included the following: telehealth in an Australian child adolescent mental health clinic (de Kam, 2020); an online family-based prevention program in the US (Cohen & Tisch, 2021); virtual social work care with older black adults in Canada (Giwa, Mullings, & Karki, 2020); a social media campaign in Lebanon titled “Humans discriminate, Viruses don’t” (Badran, 2020); and the use of the Internet to care for cadets by military social workers in Taiwan (Chiu & Yu, 2020). Technology training and creative strategies would be necessary for social workers to assist older adults in learning and using new telehealth and social engagement technologies (Gibson et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A recent longitudinal adolescent study in US found that before COVID-19, almost all parents forbade adolescent drinking with the family, but data collected during the lockdown showed that 1 in 6 allowed it [ 17 ], with parents who drank heavily being more lenient in allowing adolescent drinking during lockdown. Interventions to support parental alcohol use could have secondary benefits to children’s health, and family-based interventions could be an effective treatment option for addressing substance use in both parents and adolescents [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond service delivery, purveyors and developers may find that certain core components cannot be delivered remotely, leading to adaptations that compromise the essential activities proven necessary to achieve intended outcomes. Furthermore, Cohen and Tisch ( 2021 ) noted that shifting from in-person to an online model is not a simple undertaking; adopting a virtual approach requires a high level of technical skill for interventions to still be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is a need for research on the processes and outcomes of adapting interventions originally designed for in-person interaction to an online mode (Cohen & Tisch, 2021 ). Intervention developers and other researchers should be designing outcome evaluations to examine whether these translational efforts undermined intervention integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation